College Students' Need for Cognition, Academic Motivation, Performance, and Well-Being - Fagela-Tiangco, Cristabel (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Students (N=48) enrolled in a higher Psychology course participated in this study by answering the Need for Cognition Scale (NCS), Academic Motivation Scale (AMS), and Psychological Well-Being Scales (PWBS). The average of the percentage scores in the midterm and final examinations was used as an indicator of academic performance. Data were analyzed using Pearson product moment correlations. Academic motivation was found to correlate significantly with three dimensions of well-being (environmental mastery, personal growth, purpose in life) and need for cognition, but not with academic performance. One important implication of this study is that nurturing certain dimensions of wellbeing can improve motivation in our students. Thus, one of possible interventions for students-at risk due to lack of motivation in their studies would be a program addressing such well-being dimensions.